Human immunodeficiency virus-associated neurocognitive disorders (HAND) - Guevara Silva, Erick (2014)
HIV-associated neurocognitive disorder (HAND) is not a well recognized entity but has high prevalence and impact in individuals infected with HIV. The term HAND encompasses a spectrum of progressive central nervous system (CNS) involvement, ranging from asymptomatic neurocognitive impairment and minor neurocognitive disorder through to the most severe form of HIV-associated dementia (HAD). While the incidence of HAD has declined significantly with highly active antiretroviral treatment (HAART), the milder forms of HAND have increased. In this review, updated nomenclature and research case definitions to guide HAND diagnosis are described. Clinical manifestations, diagnosis and treatment recommendations are also outlined. Finally, while neurocognitive impairment is typically diagnosed with full neuropsychological evaluation, the interpretation of test results is based on comparing the patient’s performance to age and culturally adjusted population based normal values; thus, test results are valid only if adequate representative normative data exist for a given patient. Therefore, we propose a group of brief neuropsychological tests validated in Peruvian population that could be used to detect HAND opportunely not only by neurologists but also by a primary HIV-care provider or in resource-poor settings.